Multi-sectoral nutrition policy and programme design, coordination and implementation in Ethiopia - Ayele, Seife; Zegeye, Elias Asfaw; Nisbett, Nicholas (Institute of Development Studies, 2020)
Multi-sectoral nutrition governance has been hailed as an effective mechanism to reduce undernutrition. Ethiopia has adopted the approach and has been implementing nutrition programmes with some success, but undernutrition remains high for a range of reasons. This study explores political economy challenges facing Ethiopia in nutrition programme design, coordination and implementation, and looks at root causes that remain less understood. Using reviews of literature, qualitative interviews and a deep-dive study of two interventions, the study finds that the policy narrative has shifted in Ethiopia from the historically dominant narrative of ‘food and production security’ to ‘food and nutrition security’. The former ad hoc and reactive responses to droughts and famines have given way to an understanding of the complexity of undernutrition, its causes and consequences. However, in several critical areas, multi-sectoral nutrition coordination under the federal Ministry of Health, and regional bureaux of health, has been ineffective for many reasons, including lack of accountability mechanisms; perceived coordinator bias; inadequate staffing and resources; and low priority often given to programmes, which results in undernutrition – the ‘silent problem’ – being side-lined to ‘competing priorities’. As envisaged in the Food and Nutrition Policy, the study recommends setting up a well-equipped, and independent, multisectoral governance structure, and offers several recommendations that can reinvigorate the process towards sustainably reducing undernutrition.